Cytocompatibility Evaluation of Hydroxyapatite Coating on Titanium Surfaces by Pulsed Electrochemical Deposition - Liu, Cunping; Yang, Yanxiong (Asian Journal of Chemistry, 2014)
Hydroxyapatite coating was prepared on titanium substrate by pulsed electrochemical technology, in which the Ca/P ratio was 1.67 and the pH was adjusted by dilute HNO3 and NH4OH to 6.0. The X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy were used to investigate microstructure and morphology of the materials. Then, effects of hydroxyapatite coating on the MC3T3-E1 osteoblastic cells were investigated by MTT assay method to evaluate cytocompatibility of the new scaffold. Results indicate that the prepared hydroxyapatite coating has great potential to be used as bone substitution material compared with pure titanium because of its good mechanical properties, eligible cytotoxicity and good cytocompatibility.